English instruction challenges and opportunities in Indonesian primary schools: A systematic review - Daud, Afrianto (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
This study aims to examine the challenges, opportunities, and future directions of teaching English at primary schools in Indonesia through a systematic literature review. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic search was conducted across multiple academic databases, including Google Scholar, ERIC, and ScienceDirect. Two independent reviewers screened titles and abstracts, and subsequent full-text reviews were performed to confirm eligibility. After the systematic selection process, 11 articles were finally included in this study, providing valuable insights into the challenges and opportunities associated with teaching English at primary schools in Indonesia. This study found that English teaching at primary schools in Indonesia is confronted with various challenges ranging from a shortage of qualified English teachers, changes in language policy, limited learning resources, and limited time allotment to limited exposure to English. Despite the challenges, this study reveals that there are some opportunities, such as the high demand for English learning from the community and the new Emancipated Curriculum policy reopening doors for English lessons at primary schools. These findings offer insights on how the English teaching at primary schools in Indonesia should be managed in the future.